Application of green first derivative synchronous spectrofluorometric method for quantitative analysis of fexofenadine hydrochloride and pseudoephedrine hydrochloride in pharmaceutical preparation and spiked human plasma - Sherif Ramzy; Ahmed H. Abdelazim; Mohamed A. Hasan (BMC Chemistry, 2022)
Abstract Fexofenadine hydrochloride and pseudoephedrine hydrochloride are prescribed in a combined dosage form for the treatment of allergic rhinitis. In the present work, a sensitive synchronous fluorescence spectroscopic method was applied in conjunction with first derivative for quantitative estimation of fexofenadine hydrochloride and pseudoephedrine hydrochloride in pure form, pharmaceutical tablets and spiked human plasma. Fexofenadine hydrochloride showed its conventional emission spectrum at 294 nm when excited at 267 nm. On the other hand, pseudoephedrine hydrochloride showed its conventional emission spectra at 286 nm when excited at 261 nm. The fluorescence intensities were greatly enhanced by the use of sodium dodecyl sulphate as a micellar surfactant. Application of the synchronous mode to measure the fluorescence spectra of the above drugs provided sharp narrowing bands, but the overlap was not completely resolved. Derivatization of the synchronous spectra to the first order completely resolved the overlap of the fluorescence spectra and allowed simultaneous quantitative determination of the drugs under study. Fexofenadine hydrochloride and pseudoephedrine hydrochloride could be determined from their first-order synchronous spectra at 286 and 294 nm, respectively, without interfering with each other. The method showed linearity with an excellent correlation coefficient in the concentration range of 100–1500 ng/mL for Fexofenadine hydrochloride and 50–1000 ng/mL for pseudoephedrine hydrochloride. The method was successfully applied for the simultaneous determination of the studied drugs in pharmaceutical formulation, with mean percent recoveries for Fexofenadine hydrochloride and pseudoephedrine hydrochloride of 99.49 ± 0.931 and 98.67 ± 0.634, respectively, and in spiked human plasma, with mean percent recoveries for Fexofenadine hydrochloride and pseudoephedrine hydrochloride of 95.21 ± 1.938 and 94.89 ± 1.763, respectively. Furthermore, the greenness of the described method was assessed using four different tools namely, the national environmental method index, the analytical eco-scale, the green analytical procedure index and the AGREE evaluation method. The proposed method seemed to be superior to the reported HPLC method with respect to the metrics of the greenness characters.